Trends in reported antibiotic use among children under 5 years of age with fever, diarrhoea, or cough with fast or difficult breathing across low-income and middle-income countries in 2005–17: a systematic analysis of 132 national surveys from 73 countries. Issue 6 (June 2020) - Allwell-Brown, Gbemisola; Hussain-Alkhateeb, Laith; Kitutu, Freddy Eric; Strömdahl, Susanne; Mårtensson, Andreas; Johansson, Emily White
Summary: Background: Global assessments of antibiotic consumption have relied on pharmaceutical sales data that do not measure individual-level use, and are often unreliable or unavailable for low-income and middle-income countries (LMICs). To help fill this evidence gap, we compiled data from national surveys in LMICs in 2005–17 reporting antibiotic use for sick children under the age of 5 years. Methods: Based on 132 Demographic and Health Surveys and Multiple Indicator Cluster Surveys from 73 LMICs, we analysed trends in reported antibiotic use among children under 5 years of age with fever, diarrhoea, or cough with fast or difficult breathing by WHO region, World Bank income classification, and symptom complaint. A logit transformation was used to estimate the outcome using a linear Bayesian regression model. The model included country-level socioeconomic, disease incidence, and health system covariates to generate estimates for country-years with missing values. Findings: Across LMICs, reported antibiotic use among sick children under 5 years of age increased from 36·8% (uncertainty interval [UI] 28·8–44·7) in 2005 to 43·1% (33·2–50·5) in 2017. Low-income countries had the greatest relative increase; in these countries, reported antibiotic use for sick children under 5 years of age rose 34% during the study period, from 29·6% (21·2–41·1) in 2005 to 39·5% (32·9–47·6) in 2017, although it remained the lowest of any income group throughout the study period. Interpretation: We found a limited but steady increase in reported antibiotic use for sick children under 5 years of age across LMICs in 2005–17, although overlapping UIs complicate interpretation. The increase was largely driven by gains in low-income countries. Our study expands the evidence base from LMICs, where strengthening antibiotic consumption and resistance surveillance is a global health priority. Funding: Uppsala Antibiotic Centre, Uppsala University, Uppsala University Hospital, Makerere University, Gothenburg University.